RIWAYAT STATUS GIZI IBU HAMIL DENGAN KEJADIAN STUNTING - Dwi Astuti; Atun Wigati; Ana Zumratun Nisak; Noor Azizah; Irawati Indrianingrum (Universitas Muhammadiyah Kudus, 2024)
Background: The incidence of stunting in infants is currently quite high, the World Health Organization (WHO) estimates the prevalence of stunting worldwide at 22 percent or as many as 149.2 million in 2020. The prevalence of stunting in Indonesia is currently still at 24.4 percent or 5.33 million children under five. Objective: Analyze the relationship between maternal nutritional status during pregnancy to the incidence of stunting at the Pecangaan Health Center, Methods: correlation research with retrospective approach. Purposive sampling technique with 33 stunted mothers and toddlers 2-5 years old at the Pecangaan Health Center. Primary data collection was carried out by measuring the BB and TB of toddlers when checking with a checklist. Results: The incidence of stunting in toddlers is mostly short toddler conditions as much as 22 (66.7%). The nutritional status of mothers during pregnancy is mostly mild emaciation conditions as much as 18 (54.5%). The results of bivariate analysis of maternal nutritional status during pregnancy and the incidence of stunting in toddlers at the Pecangaan Health Center were obtained p (0.001). Conclusion: There is a relationship between the nutritional status of mothers during pregnancy and the incidence of stunting in toddlers at the Pecangaan Jepara. Pregnant women pay more attention to their pregnancy with good nutritional intake and routine pregnancy control